Investor reaction to R&D investment: Are new product announcements and development capacity missing links?. Issue 2 (6th June 2016) - Li, Xin; Wang, Tienan
Abstract : Purpose: This paper aims to examine the impact of research and development (R&D) investment on firms' stock price from the perspective of investors. Design/methodology/approach: Building on signaling theory, the authors propose that R&D investment sends important signals to the investment community regarding future growth, which in turn impacts investor reaction to such investment. Findings: Using a sample of listed pharmaceutical firms in China from 2007 to 2011, the authors find that R&D investment has a positive effect on firms' stock price, indicating that investors have a positive reaction to R&D investment signals. Further, the authors find that the signaling role of new product announcements mediates this relationship between R&D investment and investor reaction. Originality/value: The authors also find that the signaling role of development capacity (DC) has a moderating effect on the relationship between innovation activities (i.e. R&D investment and new product announcements) and investor reaction, such that DC strengthens the positive effect of R&D and new product announcements on investors.